Mapping the Intellectual Landscape of Sustainable Finance: A Bibliometric Analysis - Loso Judijanto (Sciences du Nord Economics and Business, 2025)
This study presents a comprehensive bibliometric analysis of the evolving field of sustainable finance, aiming to map its intellectual structure, thematic trends, and collaborative networks. Drawing on a dataset of scholarly publications indexed in the Scopus database from 2000 to 2024, the study employs VOSviewer to conduct co-authorship, country collaboration, keyword co-occurrence, temporal overlay, and density visualizations. The analysis identifies "sustainable development" as the central thematic node, with closely associated topics including green finance, ESG investment, economic development, and innovation. Emerging areas such as decentralized finance, financial inclusion, and green development highlight a shift toward technology-enabled and socially inclusive financial paradigms. Author and country networks reveal regional clustering, particularly in China, the United States, and Western Europe, while also indicating limited cross-regional integration. Temporal analysis shows a clear evolution from traditional finance-based approaches to broader interdisciplinary concerns. These findings provide valuable insights into the structure and trajectory of sustainable finance research and underscore the need for expanded collaboration, thematic diversification, and integration of perspectives from the Global South. The study contributes to a more strategic and inclusive understanding of how finance can be leveraged to achieve global sustainability goals.